Minimum wage: Many entitled employees in Germany still do not receive it - Alexandra Fedorets; Markus M. Grabka; Carsten Schröder (DIW Weekly Report, 2019)
There has been a universal statutory minimum wage in Germany for a good four years, but many employees still do not receive it. This is the finding of new calculations based on the Socio-Economic Panel (SOEP), which have updated noncompliance with the minimum wage for 2017. Even conservative calculations indicate that around 1.3 million people who are entitled to the minimum wage receive a lower wage in their main employment. And they are joined by around a half a million persons in secondary employment. The contractually agreed wages of the ten percent of employees with the lowest wages did indeed rise by around 13 percent between 2014 and 2016. But despite the first-time minimum wage hike to 8.84 euros in 2017, the positive trend did not continue. The extent to which the decision of the European Court of Justice, which obligates employers to record all of the hours worked by employees, can curb noncompliance with the minimum wage depends on how the decision is implemented in practice. Further, the implementation of a 'fair-pay label' to identify companies that can provide traceable documentation of their compliance with the minimum wage is recommended. As with organic certification, such a seal would enable consumers to make conscious informed decisions about which products and services from which manufacturers and providers to buy.
Keywords: B41; C83; D31; J31; 330; minimum wage; inequality; employment; SOEP